2019
DOI: 10.1017/s0958344019000065
|View full text |Cite
|
Sign up to set email alerts
|

Mobile-assisted language learning: A Duolingo case study

Abstract: The growing availability of mobile technologies has contributed to an increase in mobile-assisted language learning in which learners can autonomously study a second language (L2) anytime or anywhere (e.g. Kukulska-Hulme, Lee & Norris, 2017; Reinders & Benson, 2017). Research investigating the effectiveness of such study for L2 learning, however, has been limited, especially regarding large-scale commercial L2 learning apps, such as Duolingo. Although one commissioned research study found favorable lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
160
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 227 publications
(180 citation statements)
references
References 22 publications
15
160
0
5
Order By: Relevance
“…Interestingly, one learner stated that certain mobile educational applicationssuch as British Council App, supported the learners to track their daily learning progress and offers -a reward like if we could achieve some goals from that games‖ (Mawar). This finding is consistent with that of [18] who mentioned the positive aspect of gamification in Duolingo, a foreign language learning application. However, a note of caution is due here since paying the test in advance and planning their IELTS practice timetable and progress can, therefore, be assumed as intrinsic motivation.…”
Section: B Rq 2: Self-directed Mobile Learning Strategies For Ielts supporting
confidence: 91%
See 4 more Smart Citations
“…Interestingly, one learner stated that certain mobile educational applicationssuch as British Council App, supported the learners to track their daily learning progress and offers -a reward like if we could achieve some goals from that games‖ (Mawar). This finding is consistent with that of [18] who mentioned the positive aspect of gamification in Duolingo, a foreign language learning application. However, a note of caution is due here since paying the test in advance and planning their IELTS practice timetable and progress can, therefore, be assumed as intrinsic motivation.…”
Section: B Rq 2: Self-directed Mobile Learning Strategies For Ielts supporting
confidence: 91%
“…They reported that several tools and apps in their smartphone, for examples, YouTube, Spotify 1 , Podcast 2 , and Web Browser enable them to practice their listening and reading skills more conveniently across time and spaces, for examples, while waiting for the doctor, commuting by train or bus, and riding on a motorbike. This connects with Loewen et al's findings [18] who supported that the use of mobile phones had greatly advantaged their research participants to learn foreign languages in flexible ways anytime and anywhere.…”
Section: A Rq1: Advantages and Challenges Of M-learning 1) Efl Learnsupporting
confidence: 76%
See 3 more Smart Citations